Skin diseases and conditions among students of a medical college in southern India - Nitin Joseph; Ganesh S Kumar; Maria Nelliyanil (Indian Dermatology Online Journal, 2014)
Introduction: Skin diseases are a common problem among young adults. There is paucity of data about it among medical students. This study aimed to find out the pattern of skin disorders and to describe their association with various socio-demographic factors among medical students. Materials and Methods: This cross-sectional study was conducted in June 2011 in a medical college in Mangalore, Karnataka. Two-hundred and seventy eight medical students were chosen from the 4 th , 6 th and 8 th semester through convenient sampling method. Data on hair and skin morbidities suffered over past 1 year and its associated factors were collected using a self-administered questionnaire. Results: Most of the participants 171 (61.5%) were of the age group 20-21 years and majority were females 148 (53.2%). The most common hair/skin morbidities suffered in the past one year were acne 185 (66.6%), hair loss 165 (59.3%), and sun tan 147 (52.9%). Fungal infection (P = 0.051) and severe type of acne (P = 0.041) were seen significantly more among males while hair morbidities like hair loss (P = 0.003), split ends of hairs (P < 0.0001) and dandruff (P =0.006) were seen significantly more among female students. Patterned baldness (P = 0.018) and sun tan (P < 0.0001) were significantly more among non-Mangalorean students than native Mangaloreans. Presence of dandruff was significantly associated with hair loss (P = 0.039) and usage of sunscreen was found to protect from developing sun tans (P = 0.049). Conclusion: Skin disorders, particularly the cosmetic problems are very common among medical students. Gender and place of origin were found to significantly influence the development of certain morbidities.